School segregation: theoretical insights and future directions. Issue 1 (2nd January 2022) - Perry, Laura B.; Rowe, Emma; Lubienski, Christopher
ABSTRACT: School segregation is both an enduring and growing area of research interest. School segregation is shaped by multiple and complex forces within educational ecosystems, including individual students and households, education jurisdictions, organisational (dis)incentives, policies, and larger societal characteristics and contexts. As a field of study, comparative education emphasises the complex interactions of historical and socio-cultural context with actors, social institutions and policy settings for explaining educational phenomena. With this foundation, comparative education is uniquely positioned to integrate studies of school segregation into a comprehensive and comparative framework for deepening our theoretical understanding of school segregation and its causes, solutions, and impacts on educational equity. This paper introduces the special issue on school segregation. In addition to providing an overview of the special issue, we present a theoretical framework that may be useful for informing future comparative studies and conclude with several possible future research directions.